Physicochemical Properties of Baobab Seeds (Adansonia digitata) Crude Oil and Its Use in Food Frying - Alpashir, Altayp Abdalrahman Altayp; Saad Shakak, Mahdi Abbas (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
This study was conducted to recognize the physical and chemical properties of baobab seeds crude oil and its use in food frying process. The seeds were milled for proximate analysis: oil content, protein content, moisture content, total ash, crude fiber, and carbohydrate, then the results were recorded 27.5%, 14.0%, 5.7%, 3.4%, 15.0%, 34.4% respectively. The oil was extracted by mechanical pressing, then the physical properties density, viscosity, refractive index, and moisture content were tested, the results were recorded 0.9139, 22.6 cp, 1.4690, 0.1% respectively. Also the chemical properties peroxide value, free fatty acids, saponification value, and iodine value, were determined, the results were recorded 9.0 meqo2/kg, 1.8%, 240.4, 54.0 respectively. The fatty acids composition were determined as oleic acid, linoleic acid, palmitoliec acid, palmitilaidic acid, palmitic acid, stearic acid, arachidic acid, lauric acid, capric acid, and others, the results were recorded25.7, 30.1, 0.2, 1.3, 17.8, 1.0, 1.4, 0.03, 0.04%, and 22% respectively. The statistical analysis showed that there was significant difference (P 0.05) in physical properties moisture content 0.2, viscosity 26.6, of baobab seeds crude oil after first frying compared with a refined commercial edible oil 0.1, 23.7,respectively, while there was no significant difference (P 0.05) in density 0.9 123,refractive index 1.4700, of baobab seeds crude oil after first frying compared with a refined commercial edible oil 0.9164, 1 .4730 respectively, also the statistical analysis showed that there was significant difference (P 0.05) in viscosity 38.3cp of baobab seeds crude oil after second frying compared with a refined commercial edible oil 25.9, while there was no significant difference in moisture content 0.2, density 0.9170, and refractive index 1.4700, of baobab seeds crude oil after second frying compared with a refined commercial edible oil 0.1, 0.9158, 1.4740 respectively. Also there was no significant difference in chemical properties peroxide value 9.0, of baobab seeds crude oil before frying compared with a refined commercial edible oil 9.0, also there was no significant difference in peroxide value 12.9 of baobab seeds crude oil after second frying compared with refined commercial edible oil 15.9, while there was significant difference in peroxide value 9.9, of baobab seeds crude oil after first frying compared with a refined commercial edible oil 13.9. The statistical analysis showed that there was significant difference in free fatty acids 1.8, 1.9, 1.7 of baobab seeds crude oil before and after first and second frying compared with refined commercial edible oil 0.6, 0.6, 0.6 respectively. The statistical analysis showed that there was no significant difference in organoleptic test color, texture, flavor, taste, and acceptability of potato fried by baobab seeds crude oil after first and second frying compared with the refined commercial edible oil.